International Military Medical Engagement with the Indigenous Civilian Health Sector. Issue Volume 157:Issue (2011)Supplement 4 (1st December 2011) - Bricknell, Martin CM; Cameron, E
Abstract : This paper examines the engagement of international military medical services with the indigenous health sector. It focuses on the relationship between security forces, both international and indigenous, with the indigenous civilian health sector based on experiences and observations at the operational and tactical level from engagement with the Afghan civilian health sector in 2009/10. The paper provides a practical description of medical engagement within the 'Shape-Clear-Hold-Build-Transfer' construct for counter insurgency operations.